Functionalized ?6-arene ruthenium complexes - Therrien, Bruno (My University, 2009)
A review. ?6-Arene Ru complexes were known for >30 years, and their chem. was extensively studied for unfunctionalized arenes such as benzene, para-cymene and hexamethylbenzene. However, little is known about ?6-arene Ru complexes in which the arene ligand is not merely an arom. hydrocarbon but contains chem. functions as substituents. This paper gives an overview of functionalized ?6-arene Ru complexes, their syntheses and structures, as well as their intrinsic potential ranging from biol. applications to applications as nano-materials. [on SciFinder(R)]
Keywords: review functionalized arene ruthenium complex prepn structure application